Critical Review of Changes from Classical to Contemporary Contracts in Sharia Economic Transactions: Fiqh Perspective - Husein Lubis, Rahmat; Yuniar Pradini, Anez (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2024)
This research aims to analyze the form of legal contract principles in Islamic alliances mu'amalah. A deep agreement mu'amalah cannot be separated from the Islamic community. An alliance occurs because of a meeting between the two parties at the same time to tie a promise. In the field alliance, alliance will be needed to achieve common goals. Civil Code Article 1233 states that an agreement occurs with agreement and law. This research is a type of qualitative research with a small library. The data used are primary and secondary data types. Primary data comes from literature such as scientific works, books, websites, etc. And for secondary data, there are books that support the core of this research. This research's analytical method uses an inductive analysis method. The results of this research found that the study of sharia economic law relating to the form of principles of multipurpose engagement agreements consists of; Divine principle, principleworship, principle of freedom of contract, principle of consensualism, principle of binding, principle of balance, principle of benefit, principle of trust, principle justice, and principles of writing.